Introducing Inharmonic Radar: Tag Detection in the Automotive Bands of Present and Future at 76–81/134–141 GHz via Fractional Multiplication - Tobias T. Braun; Jan Schopfel; Christian Bredendiek; Juan Jose Forero B.; Nils Pohl (IEEE Journal of Microwaves, 2024)
Harmonic radar systems are highly effective at distinguishing specific targets from surrounding clutter. Therefore, the reception of a tag response, conventionally at the second harmonic, is utilized. Thus, necessitating two bands with that specific spacing allocated to the same application. Among others, this is not the case for automotive, where tag-based detection of vulnerable road users in city traffic has shown promising results. Therefore, we introduce the novel nonlinear radar category of inharmonic radar. It is based on fractional multiplication, to enable a wider range of possible factors. Specifically, the automotive band at 76–81 GHz is connected with the 134–141 GHz frequency range by a factor of 1.75. The realized system achieves a clutter rejection of 60 dB, which is investigated in detail regarding influences of the inharmonic approach. Detection of the corresponding tag is successfully achieved up to a distance of 28 m with compliance for automotive radar, while no significant spectral purity degradation is caused by the unique frequency conversion.